PREFERENSI NASABAH PEGADAIAN SYARIAH - RUSDIYAH, RUSDIYAH (Islamic Economics and Business Faculty of UIN Antasari, 2014)
The existence of Sharia mortgage is initially supported by the success of Islamic Banking and the Muslims necessary of the existence of mortgage principled with sharia. Nowadays, motivation of Muslims for transaction is not only influenced by religious motivation, but also on their attitudes and perceptions, such as relative advantage, location and others. It becomes a question to society in Banjarmasin, who are predominantly Muslim, whether religious factors or other factors are more dominant to influence the preferences of clients (attitudes and motivation) in transactions in Shariah mortgage Kebun Bunga branch office, Banjarmasin.